Volumetric Parameters Changes of Sequential 18F-FDG PET/CT for Early Prediction of Recurrence and Death in Patients With Locally Advanced Rectal Cancer Treated With Preoperative Chemoradiotherapy. (December 2015) - Kim, Seong-Jang; Chang, Samuel
Abstract : The goal of the present study was to determine whether volumetric parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) measured by sequential 18 F-FDG PET/CT imaging could be used as prognostic factors in patients with locally advanced rectal cancer (LARC) who received preoperative concurrent chemoradiotherapy. Methods: A total 64 patients with LARC patients were included in the current study. All patients were evaluated by 18 F-FDG PET/CT before and after 45 Gy of radiotherapy with concurrent oral capecitabine chemotherapy. Initial, second, and the percent changes ([INCREMENT], %) of semiquantitative and volumetric parameters were used to calculate recurrence-free survival (RFS) and overall survival (OS). The cutoff values of semiquantitative and volumetric parameters were determined by receiver operating characteristic curve analysis. The prognostic significance was assessed using univariate and multivariate Cox proportional hazard regression analysis. Results: For RFS, American Joint Committee on Cancer (AJCC) stage (χ 2 = 10.7, P = 0.002), surgical margin (+) (χ 2 = 3.39, P = 0.037), lymphatic invasion (+) (χ 2 = 6.8, P = 0.0078), RECIST (Response Evaluation Criteria in Solid Tumors) (χ 2 = 46.3, P < 0.0001), SUVmax1 (χ 2 = 10.1, P = 0.025), ΔSUVmax (χ 2 = 20.4, P < 0.0001), ΔSUVmean (χ 2 = 28.8, P < 0.0001), MTV1 (χ 2 = 24.1, P < 0.0001), ΔMTV (χ 2 = 27.4, P < 0.0001), TLG1 (χ 2 = 21.9, P < 0.0001), TLG2 (χ 2 = 23.3, P < 0.0001), and ΔTLG (χ 2 = 55.6, P < 0.0001) are associated prognostic factors. For OS, AJCC stage (χ 2 = 6.0, P = 0.021), surgical margin (+) (χ 2 = 3.2, P = 0.042), lymphatic invasion (+) (χ 2 = 3.8, P = 0.048), RECIST (χ 2 = 10.4, P = 0.0015), ΔSUVmax (χ 2 = 6.0, P = 0.013), ΔSUVmean (χ 2 = 10.5, P = 0.0009), MTV1 (χ 2 = 14.5, P = 0.0008), ΔMTV (χ 2 = 14.7, P = 0.0002), TLG1 (χ 2 = 15.8, P = 0.0002), TLG2 (χ 2 = 13.5, P = 0.0006), and ΔTLG (χ 2 = 17.5, P < 0.0001) are potent predictors. Multivariate Cox proportional hazard regression analyses revealed that the initial MTV (MTV1) and ΔTLG were the potent predictors for RFS and OS. Conclusions: Our data suggest that MTV on initial pretreatment 18 F-FDG PET/CT and ΔTLG of sequential 18 F-FDG PET/CT after preoperative concurrent chemoradiotherapy in LARC patients could provide prognostic information.